Modeling Cell-Cell Interactions in Parkinson's Disease Using Human Stem Cell-Based Models. - Rizo Garza, Tania; Simmnacher, Katrin; Lanfer, Jonas; Rizo, Tania; Kaindl, Johanna; Winner, Beate (Frontiers in Cellular Neuroscience, 2019)
models of PD, focusing on those phenotypes that have been detected in genetic and sporadic PD models. An additional point covered in this review will be the use of induced pluripotent stem cell (iPSC)-derived technologies to model cell-cell interactions in PD.